Simulation of the Hydrodealkylation of Toluene Using Conversion Reactor - Agustriyanto, Rudy; Setyopratomo, Puguh; Mochni, Endang Srihari; Purwanto, Edy (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2024)
Abstract—The hydrodealkylation of toluene is frequently used to produce the more valuable compound benzene. This process is widely employed in the petrochemical industry. Through hydrodealkylation, toluene undergoes a transformation, resulting in the production of valuable chemicals such as benzene and diphenyl. The objective of this study is to present the results obtained from simulating the process of toluene dealkylation using Aspen HYSYS. The feed to the reactor must contain toluene and hydrogen, while the recommended operating conditions are at 500 oC to 650 oC and 20 to 40 atm pressure to achieve 90% conversion. For this purpose, a conversion reactor has been selected as the preferred type. The simulation outcomes are particularly valuable during the initial stages of designing a production facility for benzene. The mass and energy balance calculations can be easily performed using Aspen HYSYS. Future research may focus on investigating different reactor types while considering the kinetics of the reaction. Keywords: aspen HYSYS, hydrodealkylation, simulation, toluene Abstrak—Hidrodealkilasi toluena sering digunakan untuk menghasilkan senyawa yang lebih bernilai yaitu benzene. Proses ini banyak digunakan dalam industri petrokimia. Melalui hidrodealkilasi, toluena mengalami transformasi, menghasilkan bahan kimia berharga seperti benzene dan diphenyl. Tujuan dari penelitian ini adalah untuk menyajikan hasil yang diperoleh dari mensimulasikan proses dealkilasi toluena menggunakan Aspen HYSYS. Umpan ke reaktor harus mengandung toluena dan hidrogen, sedangkan kondisi operasi yang direkomendasikan adalah pada suhu 500 oC hingga 650 oC dan tekanan 20 hingga 40 atm untuk mencapai konversi 90%. Untuk tujuan ini, reaktor konversi telah dipilih sebagai tipe yang disukai. Hasil simulasi sangat berharga selama tahap awal perancangan fasilitas produksi benzene. Perhitungan neraca massa dan energi dapat dengan mudah dilakukan menggunakan Aspen HYSYS. Penelitian masa depan dapat fokus pada penyelidikan berbagai jenis reaktor sambil mempertimbangkan kinetika reaksi. Kata kunci: aspen HYSYS, hidrodealkilasi, simulasi, toluene